Quantum Chemical and Electrochemical Studies of Water and Ethanol Extracts of Salvadora Persica (Miswak) as a New Green Inhibitor for Dental Amalgam in Artificial Saliva - Al Maofari, A.; Akounach, Z.; Benmessaoud, M.; El Hajjaji, S. (Journal of Amran University, 2024)
Abstract The corrosion-inhibitive properties of Salvadora Persica water and ethanol extracts as a novel green inhibitor for dental amalgam in artificial saliva were studied by using potentiodynamic polarization measurements and electrochemical impedance spectroscopy measurements (EIS). The electrochemical results revealed that the Salvadora Persica extracts demonstrated strong inhibitory effects at 0.66 g/L and implied that the water extract was more effective than the ethanol extract. The inhibition efficiency (IE%) increases with increasing concentrations of both Salvadora Persica extracts and decreases with increasing temperature. The results of this work indicated that Salvadora Persica extracts act as mixed-type inhibitors, inhibiting the corrosion of dental amalgam by the adsorption process, which followed the Langmuir adsorption isotherm model. The thermodynamic results revealed that the adsorption process is endothermic with electrostatic interaction (physisorption). Various DFT parameters, like HOMO and LUMO energy, gab energy (∆E), electronegativity (χ), softness (